Cross-resistance associated with development resistance to isometamidium in a clone of Trypanosoma congolense - Peregrine, A.S.; Gray, M.A.; Moloo, S.K. (1997)
Resistance to isometamidium was increased 94-fold in a clone of Trypanosoma congolense (clone IL 1180) by repeated subcurative treatment of infected mice for 11 months. This was associated with 3.4-, 33-, and 4.2-fold increases in resistance to diminazene, homidium, and quinapyramine, respectively. Both T. congolense IL 1180 and the resistant derivative were able to undergo cyclical development in Glossina morsitans centralis tsetse flies, producing hypopharyngeal infection rates of 40.0 and 39.8 percent, respectively.